To find the polynomial identity that results from dividing \( x^2 - a^2 \) by \( x - a \), we can first recall the difference of squares identity:
\[ x^2 - a^2 = (x - a)(x + a) \]
Now, let's evaluate the options:
-
Option 1: \( x^2 - a^2 = (x - a)(x + a) \) - This matches the difference of squares identity and is correct.
-
Option 2: \( x^2 - a^2 = (x - a)(x - a) \) - This is incorrect as it does not correspond to the identity for the difference of squares.
-
Option 3: \( x^2 - a^2 = (x + a)(x + a) \) - This is also incorrect since it doesn't correspond to the factorization of \( x^2 - a^2 \).
Therefore, the correct answer is:
Option 1: \( x^2 - a^2 = (x - a)(x + a) \).